Understanding the molecular and host determinants of Powassan virus pathogenesis across cellular and animal models - Courtney, Samantha J., author; Ebel, Gregory D., advisor; Bosco-Lauth, Angela, committee member; Hemming-Schroeder, Elizabeth, committee member; Sloan, Dan, committee member (Colorado State University. Libraries, 2025)
Powassan virus (POWV) is a tick-borne flavivirus that affects the United States, Canada, and parts of Russia. Despite its capacity to cause severe and sometimes fatal neurologic disease, POWV remains poorly understood. Here, we use both cellular and animal models to investigate the molecular and host determinants of POWV evolution and pathogenesis, with a focus on recombination patterns, strain-specific disease phenotypes, and mechanisms of neurotropism. While prior studies have examined viral diversity arising from single nucleotide polymorphisms, little is known about POWV recombination, defective RNAs (D-RNAs), or functional structural variants (SVs). Understanding POWV recombination in its natural vector could offer important insights into its replication and evolution. To address this, we analyzed POWV sequence data from 53 ticks collected in the Northeastern United States to characterize and quantify recombination patterns in naturally infected ticks. We then compared these patterns to single cell culture passage isolates. Deletions were common in tick-derived POWV RNA, with several genome regions enriched for recombination junctions, which were often associated with areas of microhomology. While most deletions were unique to individual samples, two prominent deletion archetypes emerged across multiple ticks. The first involved small 19-50 base deletions in the NS5 methyltransferase domain, resulting in a mixture of putative SVs and D-RNAs. The second involved larger ~1600 base deletions spanning the NS2A-NS3 coding regions, generating putative D-RNAs that likely lack viral protease function. Interestingly, these protease deletions became significantly enriched after a single passage in baby hamster kidney cells, despite an overall decrease in deletion frequency. Together, these results demonstrate that POWV RNA recombines frequently, with particular variants more common than others. These findings may carry implications for virus immune evasion and persistence in ticks. POWV also exhibits considerable genetic and phenotypic diversity, including highly variable pathogenesis in mice. To better understand this, we investigated the genotypic and phenotypic variability of lineage II strains in C57BL/6 mice. Two New York isolates, NY.19.12 and NY.19.32, caused earlier clinical signs in mice and earlier detection of viral RNA (vRNA) in both spleen and brain compared to infections with a lineage II infectious clone (WI.97.ic). Notably, NY.19.12 and NY.19.32 share three amino acid mutations in the envelope, NS1, and NS5 proteins. These mutations were engineered into an infectious clone (NY.19.12.ic) to evaluate their contribution to pathogenesis. At six days post-infection, clinical scores, vRNA detection in the cerebellum, and viral distribution in the brain were comparable between NY.19.12 and NY.19.12.ic, suggesting these mutations may play a role in early neuroinvasion and faster disease progression. However, vRNA levels in the spleen were significantly higher in NY.19.12-infected mice compared to WI.97.ic and NY.19.12.ic, indicating that factors beyond these three mutations likely contribute to increased peripheral viral burden. Importantly, this study highlights the complexity of POWV pathogenesis and suggests that POWV lineage II strains have varying disease phenotypes likely driven by multiple genetic differences. The mechanisms by which host immune responses shape flavivirus neurotropism remain poorly understood. To address this, we used both wild-type (C57BL/6) and mitochondrial antiviral-signaling protein (MAVS) knockout mice to compare disease progression and neurotropism of POWV (lineages I and II) and West Nile virus (WNV) in the context of type I interferon signaling. We also developed and validated a comprehensive mouse model workflow for studying flavivirus CNS infection, integrating diverse inoculation routes (subcutaneous, intraperitoneal, and intracranial) with imaging techniques such as immunofluorescence assays and whole-brain imaging to map viral distribution and immune responses. MAVS knockout mice showed enhanced susceptibility, faster disease progression, and greater weight loss compared to wild-type controls, highlighting the essential role of type I interferon signaling in controlling neurotropic flavivirus infection. Additionally, a chimeric Kunjin virus displayed lower pathogenicity than WNV, supporting its use as a lower-containment model for neurotropic flavivirus research. Overall, this work provides a valuable platform for future studies on POWV pathogenesis and neurotropism, as well as for guiding therapeutic and vaccine development.
Keywords: pathogenesis; flavivirus; Powassan virus